Physiological and anthropometric characteristics of top-level youth cross-country cyclists - Fornasiero, A.; Savoldelli, A.; Modena, R.; Boccia, G.; Pellegrini, B.; Schena, F. (Journal of Sports Sciences, 2018)
In the literature there is a lack of data about the development of top level athletes in cross-country mountain biking (XCO). The purpose of this study was to analyze anthropometric and physiological characteristics of some of the best XCO bikers aged between 13 and 16. The study involved 45 bikers (26 males and 19 females) belonging to a youth national team. The evaluations, consisting of anthropometric measures, incremental cycling tests (VO2max, PPO, P@RCP), and 30 s Wingate Tests (PMax, PMean), were conducted over a lapse of 4 years. Our findings showed in bikers, already at young age, a specific athletic profile advantageous for XCO performance. At the age of 16, just before entering the junior category and competing at international level, male and female bikers showed physiological values normalized to the body mass comparable to those reported in literature for high level athletes (VO2max>70 and >60 ml/kg/min, PPO >6.5 and >5.5 W/kg, respectively in males and females). The production of high power-to-weight ratios and high peaks of anaerobic power attests the presence of highly developed aerobic and anaerobic systems in young XCO cyclists reflecting the high physiological demand of this sport.